2007
DOI: 10.1017/s0047279406000596
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalised Powerlessness? The Reality of Women's Policy Units and their Gendered Dynamics in Korea

Abstract: This study explores the gap between the rhetoric and the reality of gender mainstreaming logic, paying special attention to women's bureaux in Korea. In response to international pressures for gender mainstreaming, the Korean government has established or relocated women's bureaux since the 1990s. At first glance, it appears that the government in Korea has been keen to integrate gender issues into the entire policy process. However, closer investigation draws a very different picture. Qualitative findings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Yet the life-history method is rarely used within mainstream social policy, nor has it been deployed within the emerging field of third sector or non-profit research. Taking an anthropological approach to policy (cf Shore and Wright, 1997), this article aims to contribute to research that analyses the everyday experiences of civil servants and third sector professionals as a means of understanding policy processes (see Won, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Yet the life-history method is rarely used within mainstream social policy, nor has it been deployed within the emerging field of third sector or non-profit research. Taking an anthropological approach to policy (cf Shore and Wright, 1997), this article aims to contribute to research that analyses the everyday experiences of civil servants and third sector professionals as a means of understanding policy processes (see Won, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Turning to Korea, we also find that family policy did not receive much attention before is doubtful that feminist agency was the driving force behind family policy expansions given the limited power resources of femocrats (Won 2007), among those many came from (feminist) civil society organizations; and even women bureaucrats in the ministry conceded in interviews that they lacked the power of their labor and welfare counterparts and depended on support from the president. Also, center-left lawmakers who were sympathetic towards the confirmed that the ministry lacked the power to drive the childcare agenda, but depended on support from the president and party to overcome considerable reservations if not opposition from other government ministries; and parental leave legislation stayed with the ministry of labor.…”
Section: Family Policy and The Transformation Of The Developmentmentioning
confidence: 82%
“…In Korea, the proportion of male employees among the total number of employees taking parental leave in 2015 was only 5.6% (Kim 2016). Won (2007) argues that some Korea men feel that taking leave would put their jobs and their reputations as men at risk. In Hong Kong pressure groups believe that the risk of being unreasonably dismissed by employers affects the take-up rate of leave (Mingpao 2008).…”
Section: Insert Tablementioning
confidence: 99%